Application of short stem endoprosthesis in total hip arthroplasty in patients with haemophilia – preliminary report - Kotela, Andrzej (Medical Studies/Studia Medyczne, 2016)
Introduction: Haemophilic arthropathy is one of the most important problems in patients with haemophilia. As a consequence of multiple bleedings into the musculoskeletal system, there occur degenerative changes which lead to serious impairment of the motor system functions, and often to disability even at a young age. In the case of advanced degenerative changes of the hip joint, the treatment of choice is total hip arthroplasty (THA). One attempt of modernization of THA is the concept of metaphyseal fixation. No reports have been published to date concerning the application of a short stem endoprosthesis in total hip arthroplasty in this population. Aim of the research: To evaluate the preliminary clinical outcomes of THA using short stem endoprostheses in patients with haemophilia. Material and methods : Between January 2010 and August 2016, 38 THA procedures were performed in patients with inherited bleeding disorders. In 12 cases cementless short stem endoprostheses were applied. Nine patients had been diagnosed with severe haemophilia A and 3 patients with a severe form of haemophilia B. The mean duration of observation was 34.3 months. The post-operative outcomes were evaluated using the HHS scale, WOMAC scale, and VAS scale to assess patient satisfaction with the surgery. Postoperative complications were recorded and analysed, and radiological examination was performed. Results and conclusions : The preliminary results of THA using short stem endoprostheses are satisfactory and suggest that these implants are a reasonable and appropriate solution for patients with hip arthropathy induced by inherited bleeding disorders. Long-term follow-up is warranted.